Under the wave at Waimea - Theroux, Paul (Houghton Mifflin Harcourt, 2021)
"From legendary writer Paul Theroux comes an atmospheric novel following a big-wave surfer as he confronts aging, privilege, mortality, and whose lives we choose to remember"--